PENGARUH KECERDASAN INTELEKTUAL, EMOSIONAL DAN SPIRITUAL TERHADAP KINERJA DOSEN PADA PERGURUAN TINGGI KESEHATAN DI KOTA PALOPO - Suhandra Makkasau (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2018)
The purpose of this study is specifically: (1) To analyze the influence of intellectual intelligence, emotional intelligence, spiritual intelligence on the performance of lecturers at Health Universities located in the City Palopo. (2) To simultaneously analyze the influence of IQ, EQ, and SQ on which performance and which factors of intelligence are more influential.This type of research is classified as explanatory, namely the type of research that describes and explains the relationship between variables through hypothesis testing. in describing and explaining the data used quantitative model. The sample in this research is taken by using technique of Proporsive Random Sampling, that is taking 50% from population at lecturer at health college in palopo city. Data analysis techniques used in this study are grouped into two: descriptive analysis techniques and inferential statistical analysis techniques. In order to simplify and speed up the process of processing and calculation of research data used computer software SPSS for Windows 20 at the level of 0.05 significance.The outcomes of this research are: ISSN scientific journals that will be distributed to Higher Education of Health, especially Health College located in Palopo City. The results of this study will also be published in the form of a textbook that ISBN as an important part of scientific publications.Key Word : Intellectual, Emotional, Spiritual, Lecturers Performance